Modified dipeptide based nanospheres as a potent adjuvating delivery system for recombinant vaccines - Biswas, Saikat; Yadav, Nitin; Somanathan, Anjali; Mukherjee, Paushali; Chauhan, Virander Singh (Frontiers in Drug Delivery, 2023)
Recombinant protein vaccines offer an advantage without a safety risk in eliciting desired humoral and cell-mediated immune responses against infectious diseases. But one of their disadvantages is their low immunogenicity, thus requiring adjuvants that augment their immunogenicity. It is necessary to explore new technology that could provide a non-toxic, biodegradable, and biocompatible delivery system with adjuvant characteristics and nanotechnology provides an excellent platform for nanomaterial-based vaccine adjuvants. Here, we have synthesized a modified dipeptide, Arg-α, β-dehydrophenyalanine (RΔF) containing ΔF at its C-terminal, and characterized it using reversed-phase high-performance liquid chromatography (RP-HPLC) and mass spectrometry techniques. RΔF upon its self-assembly to spherical nanoparticles (NPs) efficiently condensed a recombinant Plasmodium falciparum surface protein, histidine-tagged MSPFu24 (Fu24H). The morphological characteristics of the nanoparticle formulation was characterized using TEM. RΔF NPs and RΔF-Fu24H complex showed excellent in vitro biocompatibility toward two mammalian cell lines and human red blood cells (RBCs). Furthermore, mice treated with R∆F NPs showed histological and haematological properties similar to the untreated control group which indicated their very high in vivo biocompatibility. Mice treated with RΔF-Fu24H nanoformulation induced a high titers of anti-Fu24H specific antibodies and showed a mixed Th1 and Th2 profile, comparable to the FDA-approved adjuvant Alhydrogel®. The sera from immunized mice inhibited the erythrocyte invasion activity of P. falciparum’s laboratory line 3D7 in vitro which was comparable to that of Alhydrogel®. The present study suggests that the highly biocompatible dipeptide-based nanoparticle formulation can further be developed and used in clinic as a promising antigen delivery platform to elicit immune responses.